Early intervention service for first episode psychosis in Modena, Northern Italy: The first hundred cases. Issue 4 (22nd January 2019) - Ferrara, Maria; Tedeschini, Enrico; Baccari, Flavia; Musella, Vincenzo; Vacca, Francesca; Mazzi, Fausto; Ferri, Mila; Srihari, Vinod; Starace, Fabrizio; ,
Abstract : Aim: To report on the development of an early intervention service in Modena, Italy, with information relevant to the first 4 years of implementation. Methods: The 2‐year service was offered to people aged 18‐35 with psychotic manifestations, within 2 years from psychosis onset/or naïve to antipsychotics, by teams placed within community mental health Centres, according to a "specialist within generalist" model. Treatment included pharmacological consultation, psychoeducation and social inclusion programs. Health of the Nation Outcome Scale was administered at baseline and every 6 months. Results: One hundred cases accepted the treatment from 1 March 2013 to 31 December 2016. Of these, 71% were male with a median age of 23. Ninety percent were diagnosed with non‐affective psychosis, yielding an estimated treated incidence of 19.1/10 5 . General practitioners (GPs)represented the most frequent referrers to the program (38%), followed by referrals from acute general and psychiatric hospital units (22%) and self‐referrals (14%). Meaningful clinical improvement was observed, 6 months after enrolment. Conclusions: An early intervention service for psychosis was successfully implemented within existing community outpatient services. GPs represented the main referrals, providing some validation of the "specialist within generalist" model of care. A promising clinical improvement and trend of reduction in duration of untreated psychosis was found, supporting the variety of early detection efforts in the community. The high median age and lack of information about pathways to care underline possible barriers to access for younger patients. These findings will inform refinement of treatments and service models for the Region.